1993
DOI: 10.1143/jjap.32.l1728
|View full text |Cite
|
Sign up to set email alerts
|

Extremely Flat Interfaces in GaAs/AlGaAs Quantum Wells Grown on GaAs (411)A Substrates by Molecular Beam Epitaxy

Abstract: GaAs/Al0.3Ga0.7As quantum wells (QWs) grown on (411)A-oriented GaAs substrates by molecular beam epitaxy (MBE) showed extremely flat interfaces over a macroscopic area (about 200 µm φ) even for the case of no growth interruption, which is mainly due to the intrinsically large migration of Ga atoms and layer growth in the step-flow mode on the (411)A plane. Photoluminescence linewidths at 4.2K were almost the same as or better than the narrowest linewidths reported for GaAs/AlGaAs and GaAs/AlAs QWs grown on GaA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
28
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(29 citation statements)
references
References 10 publications
1
28
0
Order By: Relevance
“…For example, we have reported that effectively atomically flat interfaces over a macroscopic area (''super-flat interfaces'') can be formed in GaAs/AlGaAs and pseudomorphic InGaAs/AlGaAs quantum wells (QWs) grown on (4 1 1)A-oriented GaAs substrates by molecular beam epitaxy (MBE) [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…For example, we have reported that effectively atomically flat interfaces over a macroscopic area (''super-flat interfaces'') can be formed in GaAs/AlGaAs and pseudomorphic InGaAs/AlGaAs quantum wells (QWs) grown on (4 1 1)A-oriented GaAs substrates by molecular beam epitaxy (MBE) [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Under As-rich preparation conditions the surface revealed an atomically rough structure, whose reconstruction model was derived from reconstructions known for the GaAs(001) surface [19,[22][23][24]. However, under Ga-rich conditions a transition to an extremely flat surface has been reported [24,25].…”
mentioning
confidence: 95%
“…Because of its similarity to (001), the GaAs(114) surface has been considered in early studies of heterostructures as a highly vicinal GaAs(001) surface, whose terraces extend only over a single b͑2 3 4͒-unit cell [19,20]. Moreover, this stepped morphology led to the assumption that this surface should be predestinated to accommodate strain in heterostructures [21].…”
mentioning
confidence: 99%
“…5 The In surface segregation has a large influence on the quantization energy level in the QW, which was studied by secondary ion mass spectroscopy and lowtemperature photoluminescence ͑PL͒ measurements. 6,7 Recently, we reported that effectively atomically flat interfaces over a wafer-size area ͓(411)A super-flat interfaces͔ can be formed not only in GaAs/AlGaAs QWs 8,9 but also in pseudomorphic In x Ga 1Ϫx As/Al 0.3 Ga 0.7 As QWs (xϭ0 -0.15) 10,11 grown on (411)A GaAs substrates by MBE. The formation of the (411)A superflat interfaces is strongly correlated with much enhanced surface migration of group III atoms on the (411)A plane compared with that on the ͑100͒ plane, because flatness of heterointerfaces in the (411)A GaAs/ AlGaAs QWs degrades under high As 4 pressure, 12 where surface migration of group III atoms is suppressed.…”
Section: Introductionmentioning
confidence: 99%